Are Introduced Alien Species More Predisposed to Invasion in Recipient Environments If They Provide a Wider Range of Services to Humans? - Kowiyou Yessoufou (MDPI AG, 2021)
The drivers of invasion success of alien species remain, to some extent, a matter of debate. Here, we suggest that the services (the benefits humans obtain from a species) provided by alien plants could predict their invasion status, such that alien species providing more services would be more likely to be invasive than not. The rationale for this expectation is that alien species providing multiple services stand a better chance of being introduced in various numbers and multiple times outside their native range (propagule pressure theory). We investigated this hypothesis on alien woody species in South Africa. First, we defined 12 services provided by all the 210 known naturalized alien woody plants in South Africa. Then, we tested for a phylogenetic signal in these services using a DNA barcode-based phylogeny. Finally, we tested for potential links between the services and invasion status by fitting GLM models with appropriate error families. We found a phylogenetic signal in most services, suggesting that closely related species tend to provide similar services. Counter-intuitively, we consistently found that alien non-invasive species tend to provide more services, or even unique services, in comparison to alien invasive species. Although alternative scenarios are plausible to explain this unexpected finding, we speculate that harvesting alien plants for human benefits may limit their invasion ability. This warrants further investigation.